Blockchain Based Peer-Review Interfaces for Digital Medicine - Dhillon, Vikram (Frontiers in Blockchain, 2020)
Over the last decade, strong evidence is emerging from multiple disciplines of scientific inquiry ranging from behavioral psychology to clinical medicine that many published scientific studies are not reproducible. The best-known retrospective analyses from psychology [1] and cancer biology [2] report staggeringly low replication rates of 40% and 20%, respectively. This has led to the phenomenon of a "reproducibility crisis" where a significant amount of funding, research effort and even public policy has come to depend on non-reproducible research [3]. In this perspective article, I outline how the blockchain can be used to power a decentralized peer-review system for digital health applications. This is followed by a discussion of how such a system impacts the broader issue of scientific reproducibility, and how existing blockchain protocols can help alleviate the barriers to reproducibility.